The taxonomic status of Leptodactylus geminus Barrio, 1973 - Kwet, A.; Di-Bernardo, M.; Garcia, PCA (Soc Study Amphibians Reptiles, 2001)
The advertisement calls of Leptodactylus geminus, Leptodactylus gracilis, Leptodactylus plaumanni, and Leptodactylus fuscus are analyzed and compared with published reports. Based on calling data and examination of type material, Leptodactylus geminus is synonymized with L, plaumanni. To differentiate between the sibling species L. gracilis and L. plaumanni, fieldwork is needed, including recording of advertisement calls. Reliable identification of red specimens is not possible based on morphology and coloration alone.